2010
DOI: 10.1007/bf03391594
|View full text |Cite
|
Sign up to set email alerts
|

Communicable Diseases: Achievements and Challenges for Public Health

Abstract: The past two centuries have seen enormous achievements in control of infectious diseases, previously the leading cause of death, in large measure due to sanitation and food safety, vaccines, antibiotics and improved nutrition. This has led people to put their faith in the notion that medical science would succeed in overcoming the remaining obstacles. Vaccination has eradicated smallpox, nearly eradicated poliomyelitis and greatly reduced many other highly dangerous infections such as diphtheria, tetanus and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…29,39 Nevertheless, the recent pandemic alarm in 2009, plus ongoing outbreaks of emerging influenza strains in other countries, such as A(H5N1) and, most recently, A(H7N9), as well as the number of deaths and complications in some regular influenza seasons, have increased the interest in influenza control in the area. To address the growing need for more affordable and accessible influenza vaccines during a pandemic, WHO has assisted countries in Asia (India, Indonesia, Thailand and Viet Nam) in developing their domestic vaccine production capacity.…”
Section: Discussionmentioning
confidence: 99%
“…29,39 Nevertheless, the recent pandemic alarm in 2009, plus ongoing outbreaks of emerging influenza strains in other countries, such as A(H5N1) and, most recently, A(H7N9), as well as the number of deaths and complications in some regular influenza seasons, have increased the interest in influenza control in the area. To address the growing need for more affordable and accessible influenza vaccines during a pandemic, WHO has assisted countries in Asia (India, Indonesia, Thailand and Viet Nam) in developing their domestic vaccine production capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it is conceivable that in light of current projections of unacceptable rates of tobacco-attributable morbidity and mortality for decades to come, a clinical trial of sufficient size and duration to better understand the risks and benefits of nicotine reduction would be sufficient to support implementation of such a policy. In fact, it is common in public health to address serious problems with approaches that are grounded in science, knowing that some additional evaluation and supporting research may also be needed to evaluate the impact of the policy (Centers for Disease Control andPrevention, 2011, 2012;Schlipkoter & Flahault, 2010;World Health Organization, 2012).…”
Section: Research Priorities and Types Of Studies To Address Prioritiesmentioning
confidence: 99%
“…[12] More concerted measures for a significant reduction if not elimination of infectious and other communicable diseases continue being suggested. [13] As a leading global health department, the World Health Organization (WHO) has set a target of ending some of the seemingly neglected tropical diseases by the year 2020, and apart from malaria, other diseases targeted include HAT, schistosomiasis, LF and Onchocerciasis. [6] Experts have suggested that the burden of disease in general is a function of factors in the social realm and this means there is need to look at the social dimensions of health and disease while planning for particular disease focused interventions.…”
Section: Introductionmentioning
confidence: 99%